Effects of low-purine diet supplemented with Burm. f. on growth performance, purine deposition, and biomolecules in slow-growing chickens - Orapin Jantasaeng; Michel Jacques Duclos; Kanjana Thumanu; Supattra Okrathok; Sutisa Khempaka (Animal Bioscience, 2025)
Objective This study investigated the effects of a low-purine (Pu) diet supplemented with Sida acuta Burm. f. (SA) on growth performance, serum uric acid (SUA), and meat quality, including chemical composition, biomolecules, and purine deposition, in slow-growing Korat chickens (KRC). Methods A total of 480 mixed-sex one-d-old KRC were randomly allocated into five groups with six replicates each (16 chicks/replicate) using a 1+2×2 augmented factorial experiment in a completely randomized design. Five experimental diets were as follows: a control (basal diet), two diets with 30% and 45% lower purine levels than the control (−30% and −45% Pu), each supplemented with two levels of SA (0.3% and 0.6% SA), respectively. After sex determination, all subsequent analyses were conducted exclusively on female birds. Results KRC fed a −30% Pu diet supplemented with 0.6% SA showed reduced hypoxanthine and total purine deposition in major breast muscle (Pectoralis major) without negative effects on growth performance, SUA levels, meat quality, chemical composition, biomolecules, and protein secondary structures comparable to the control group. Birds fed a −45% Pu diet, supplemented with either 0.3% or 0.6% SA, exhibited impaired growth performance and without significant changes in major breast muscle hypoxanthine or total purine content. Correlation analysis revealed that the −30% Pu diet supplemented with 0.6% SA was positively correlated with reduced hypoxanthine and total purine content, while showing negative correlations with lipid content and β-turn structure. Conclusion A 30% reduction in dietary purines combined with 0.6% SA supplementation effectively decreased purine deposition in chicken meat, contributing to the production of healthier chicken meat product. Further studies are needed to investigate the molecular mechanisms and metabolic pathways, which will enable breeders to advance the development of Pu chicken meat production.